Rational Dialogues and Its Constructive Social-Cultural Functions - Sayee, Imam Mohammad (Integrated Journal for Research in Arts and Humanities, 2024)
One of the tools that human civilizations use today to understand each other and resolve misunderstandings is dialogue. Dialogue can reduce social distances and bridge human and cultural gaps. In this research, the social and path-opening functions of dialogue as a bridge between social, political and cultural groups have been discussed. Dialogue is a dynamic process, which has two aspects of collective and social nature. Also, with the logic of dialogue and the method of conversation, it is possible to create a bridge over social, political and ethnic gaps and connect people and groups together. The purpose of writing this article is to explain and describe the functions of dialogue, whether it is possible to fill the social, gender, cultural and cognitive gaps in a society with this method. Today's democratic political systems use dialogue as a communication and cognitive bridge between themselves and the nations. Because there are many similarities between bridge and dialogue, which are also discussed in this article. Due to the fact that dialogue has a collective nature and gathering character, this research with a survey method seeks to know the importance, position and role of dialogue in reducing conflicts in social and cultural relationships. The question is, can this collective character and collection of dialogue prevent the separation and division of people and social groups and reduce misunderstandings towards each other. In addition to the theoretical part of this article, a descriptive-analytical method has been used by distributing the questionnaire. The statistical population of Badakhshan University is considered. The findings of this research indicate that dialogue is one of the appropriate ways to connect social division in a society. Based on the findings, dialogue is like a bridge, which can fill and connect social, linguistic, cultural, ethnic and political gaps. (80%) of the sample population considered the role and importance of dialogue in reducing social misunderstandings, preventing violent social, linguistic and ethnic conflicts.